Effect of biomass ash on initial sintering and fusion characteristics of high melting coal ash. (February 2021) - Fan, Hongli; Li, Fenghai; Guo, Qianqian; Guo, Mingxi
Abstract: Ash sintering and fusion characteristics are closely associated to ash-related issues. The effects of peanut hull (PH) ash on the initial sintering and fusion temperatures of high melting coal (Jiaozuo coal (JC) and Huolinhe coal (HC)) ashes were investigated. The formations of anorthite and adularia were responsible for the initial sinterings of JC and HC ashes, respectively. The increasing PH ash mass ratio caused the initial sintering temperatures (ISTs) of PH/coal ash mixtures to decrease continuously. Low ratio of PH ash addition (≤20%) decreased the IST due to the generations of low melting point (MP) potassium silicates, while high ratio of PH ash addition (30%–50%) decreased the IST owing to the melting of sylvite and the formations of new mineral phases (e.g., adularia, potassium sulfide, and diopside). When the PH ash content was ≤20%, the decrease in mullite and the increases in K-feldspar and albite greatly decreased the ash fusion temperature (AFT) of JC/PH ash mixture. The eutectic of leucite and Ca-containing silicates led to gradual decrease in the AFT of JC/PH ash mixture after 20% PH ash addition. For HC/PH ash mixture, the decrease and increase in AFT before and after the minimum were mainly ascribed to the increasing contents of low MP K-feldspar and high MP leucite, respectively. Highlights: Sintering-fusion-property change mechanisms of high melting coal ashes are studied. Biomass ash decreases the initial sintering temperatures of high melting coal ashes. Ash fusion temperature changes of high melting coal ashes present different trends. K–Al silicates play key role in the process of sintering-fusion-property variation.